The relationship between ambulance team's professional commitment, occupational anxiety, and resilience levels - İbrahim Uysal; Güneş Korkmaz; Çetin Toraman (BMC, 2024)
Abstract Background Individuals who have the ability to bounce back from stressful events, to recover from their troubles and adverse environmental conditions by getting stronger each time are known as resilient people. Some professions may cause more occupational anxiety than others due to their characteristics and working conditions. In this research, we aimed to develop a professional commitment scale for the ambulance team. Another aim was to analyze the relationships between professional commitment, occupational anxiety, resilience, gender, job, seniority and working unit variables. Methods In the study, data were collected from a total of 1142 emergency ambulance workers working in Emergency Ambulance and Emergency Call Centers in 34 different cities in Turkey. Data were collected using the "Professional Commitment of Ambulance Team Scale (PCATS), Occupational Anxiety Scale for Emergency Medical Service Professionals (OASEMSP), and Resilience Scale for Adults (RSA). Scale development analyses were carried out using Classical Test Theory (CTT) and Item Response Theory (IRT). Regression analysis were used to examine the relationships between professional commitment, occupational anxiety, resilience, gender, job, seniority and working unit. Results As a result of the exploratory factor analysis (EFA), it was determined that 8 items remaining in the professional commitment scale formed a single-factor structure, explaining 46% of the variance of professional commitment of the team. The Cronbach's Alpha reliability value was 0.867. Confirmatory factor analysis (CFA) confirmed the results of exploratory factor analysis. The Cronbach's Alpha reliability coefficient obtained through CTT was 0.868, and the marginal reliability coefficient within the scope of IRT was 0.877. The test-retest reliability coefficient was calculated as 0.832, which indicates that the scale is valid and reliable. Conclusions The study revealed that resilience has a positive effect for professional commitment while occupational anxiety has a negative effect for professional commitment. In addition, having a moderate seniority has a negative (reducing) effect for professional commitment. Other variables (gender, job, and working unit) was found to have no significant impact on professional commitment.